2019
DOI: 10.1136/vetreccr-2019-000942
|View full text |Cite
|
Sign up to set email alerts
|

Conformal hypofractionated radiotherapy for dogs with large adrenal tumours

Abstract: Adrenalectomy has been recognised as the treatment of choice for adrenal tumours. However, excision of large tumours with or without vena caval tumour thrombi is difficult. The purpose of this case series was to describe the use of 3D conformal hypofractionated radiotherapy for unresectable adrenal tumours (over 7 cm long) in three dogs (bulldog, shih tzu and miniature dachshund). The tumours had invaded the caudal vena cava in two of the dogs. The irradiation protocols included 23.7 Gy/three fractions/three w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Hypofractionated stereotactic radiotherapy for adrenal tumors with vascular invasion has been recently described in several veterinary case series, with tumors decreasing in size and dogs having survival times over a year. 13,14 This treatment, if available, is a potential alternative to surgery for dogs with adrenal tumors that are either at high risk (such as the case described in this report) or deemed inoperable.…”
Section: Discussionmentioning
confidence: 96%
“…Hypofractionated stereotactic radiotherapy for adrenal tumors with vascular invasion has been recently described in several veterinary case series, with tumors decreasing in size and dogs having survival times over a year. 13,14 This treatment, if available, is a potential alternative to surgery for dogs with adrenal tumors that are either at high risk (such as the case described in this report) or deemed inoperable.…”
Section: Discussionmentioning
confidence: 96%
“…In the present study, it was investigated whether the mobility of abdominal organs by respiration showed a significant difference between the ventral recumbency and dorsal, Rt., and Lt. lateral recumbency. In veterinary medicine, radiation therapy has often been performed in a ventral position in patients with various tumors such as heart base tumor, prostatic carcinoma, hepatocellular carcinoma, and adrenal gland tumor (13,17,19,23). In addition, as the ventral recumbency has good posture reproducibility, a control group has been set to the ventral recumbency (16).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are a few reports on radiation therapy for large adrenal tumours with intravascular invasion (Dolera et al., 2016 , Maruo et al., 2019 ), surgery is considered to be the definitive treatment for canine adrenal PHEO (Lunn & Boston, 2020 ). Two case reports have described en bloc resection, including the CVC, for canine PHEO infiltrating the CVC (Louvet et al., 2005 , Guillaumot et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%